The CAPM METHOD AS A TOOL FOR MEASUREMENT OF STOCK INVESTMENT EFFICIENCY - Nanang Rusliana; Salma Huda Aulia (Nusantara Journal Of Management Business (NUMABI), 2024)
In every investment decision, considerations such as financial information, calculations and adequate analyzes are required. This is necessary to choose stock investments that promise a level of profit with certain risks. If investors hope to obtain a high level of profit, then they must be willing to bear high risks as well. For this reason, investors should choose efficient shares in investing, namely shares that provide a certain level of profit with a minimum level of risk or that provide a certain level of risk with a maximum level of profit. CAPM is a model used to explain the relationship between systematic risk and profit levels. The expected profit is determined by the amount of systematic risk (beta), namely the sensitivity of a stock to the market. Stocks with a beta of more than one are stocks that are very sensitive to market growth, so they are called defensive stocks, namely stocks that are less sensitive to the market.